Suicide-related crisis presentations to a rural emergency department: A retrospective cohort study. (February 2023) - MacDermott, Sean; Sutton, Keith; Motorniak, David; Bredhauer, Jacqueline; Wright, Fiona; Whyte, Merryl; van Vuuren, Julia; Spelten, Evelien
Objective: The study sought to investigate the profile and characteristics of suicide-related crisis presentations and factors associated with repeat presentations to a rural hospital Emergency Department (ED). Method: This retrospective cohort study examined suicide-related crisis presentation data from a rural ED for the years 2008–2018 inclusive. Descriptive statistical analyses included demographic characteristics and trends over time. Factors associated with increased likelihood to re-present to the ED for suicide-related crisis were identified using Odds Ratio analyses. Results: First Nations People, adolescents and young adults were at increased risk of presentation. Suicidal crisis presentations had increased well beyond that which might be accorded to the catchment's population increase and almost a third of presentations involved individuals re-presenting in suicide-related crisis. Repeat presentation was positively associated with younger age, less acute triage category, discharge to the community and leaving the ED before/during treatment. Conclusions: This study illustrates the importance of flagging, follow-up and support of rural repeat presenters to reduce further suicidal behaviours and presentation. Findings support the need for culturally safe and appropriate interventions and follow-up services. It is recommended to extend approach this to non-ED settings.